P370 The thalamo-cortical generators of sleep spindles as revealed by laminar analysis of neocortex. Issue 9 (September 2017) - Hajnal, Boglarka; Ujma, Peter; Bodizs, Robert; Toth, Emilia; Eross, Lorand; Ulbert, Istvan; Cash, Sydney; Fabo, Daniel
Abstract : Introduction: Sleep spindles are generated in thalamo-cortical networks. Thalamo-cortical projections include core projections to middle and matrix projections to superficial cortical layers. It has been proposed that sleep spindles can be generated in either of these networks. Materials and methods: We used electrophysiological data recorded with subdural grid and intracortical multielectrodes in five therapy-resistant epileptic patients undergoing invasive monitoring. Spindles were detected automatically in electrocorticography channels and detection-triggered laminar microelectrode recordings were analyzed. The second spatial derivative of spindle-band filtered (band pass 10–16 Hz, 96 dB) local field potential data allowed to approximate the laminar distribution of the transmembrane generators (current source density, CSD) of spindles. The information regarding the concurrent population cellular activity was obtained by applying a high frequency band filter (500–5000 Hz, 48 dB) on epoched data. Based on the histological reconstructions of laminar electrode tracks, we could identify the precise laminar localization of current sources and sinks. Results: Results indicate highly heterogeneous intracortical local field potentials during sleep spindles, and maximum CSD in layer I, II and IV. Multi-unit activity was increased in spindle troughs as it was identified based on the spindle band filtered local field potentials. The single unit analyis revealed preferential firing of most neurons during the positive-negative phase transition of spindles. Conclusions: The results confirm that both core and matrix thalamocortical projections contribute to spindle generation, but most spindles appear to be generated by a combination of the two and only a small minority by only one or the other. Neuronal firing tracks the phase of spindles in corticographic channels. Supported by KTIA_NAP_13-1-2013-0001.